Efficacy and safety of ultrasound-guided percutaneous microwave ablation for the treatment of hepatic alveolar echinococcosis: A preliminary study. Issue 27 (July 2017) - Cairang, Yangdan; Zhang, Lingqiang; Ren, Bin; Ren, Li; Hou, Lizhao; Wang, Haijiu; Zhou, Ying; Zhang, Qingxi; Shao, Jun; Fan, Haining
Abstract : Abstract: The present study aims to assess the efficacy and safety of ultrasound-guided percutaneous microwave ablation (MWA) for hepatic alveolar echinococcosis (HAE) preliminarily. Seventeen patients diagnosed to HAE and treated with MWA (80 watts, 4 min) were retrospectively analyzed. The upper abdominal computed tomography (CT) was performed at 1, 6, 12 months after the MWA treatment. The complications were evaluated to assess the safety. The diameters of the lesions in the HAE patients ranged from 1.9 to 4.7 cm. The patients included 10 males and 7 females, aged 26 to 70 (45.82 ± 13.36) years, 5 patients infecting with chronic hepatitis viral B and 8 patients with positive hydatid antibody (IgG). The lesions observed in the postoperative CT (1, 6, 12 months) were calcified compared with those observed in the preoperative CT and without relapse. No serious treatment-related complications occurred after treatment. MWA is a novel and effective therapeutic method for HAE with a single lesion (diameter⩽=5 cm). Further studies based on prospective random control trials to confirm our findings are necessary.